低炭素鋼ラスマルテンサイトの加工硬化挙動に及ぼす固溶炭素の影響 - 小島, 真由美; 新野, 拓; 小関, 敏彦; 南部, 将一; 井上, 純哉 (鉄と鋼, 2020)
The work hardening behavior and the change in the dislocation density of lath martensite at strain levels of less than 15% under uniaxial tensile loading were investigated. It was clarified that the work hardening rate and the multiplication of dislocation become more prominent as the solute carbon content increases. The change in the mobile dislocation density during deformation was evaluated by studying dynamic strain aging behavior, and it was found that the annihilation of mobile dislocations becomes slower at a higher carbon content. The findings were further examined by a modified Kocks-Mecking-Estrin model proposed in order to explicitly clarify the changes in the mobile and sessile dislocation densities during deformation. From the model-based analysis, it is also suggested that the solute carbon retards the formation of dislocation cells by reducing the mobility of dislocations. These findings were also corresponded well with the observation of the dislocation structure using a transmission electron microscope.